Age‐specific characteristics of neutrophilic dermatoses and neutrophilic diseases in children. (28th June 2019) - Bucchia, M.; Barbarot, S.; Reumaux, H.; Piram, M.; Mahe, E.; Mallet, S.; Balguerie, X.; Phan, A.; Lacour, J.‐P.; Decramer, S.; Hatchuel, Y.; Jean, S.; et al.
Abstract: Background: Our suggested 'modern' concepts of 'neutrophilic dermatoses' (ND) and 'neutrophilic disease' were based on observations in adult patients and have not been studied in paediatric patients. Only a minority of ND occurs in children, and little is known about age‐specific characteristics. Objectives: To describe age‐specific characteristics of ND in children and to study whether our suggested 'modern' classification of ND may be applied to children. Methods: We conducted a retrospective multicentre study in a French cohort of 27 paediatric patients diagnosed with pyoderma gangrenosum (PG) or Sweet's syndrome (SS). Results: Demographics and distribution of typical/atypical forms were similar in patients diagnosed with PG and SS. Atypical ND were more frequent in infants (90%), when compared to young children (60%) and adolescents (33%). Neutrophilic disease was observed in 17/27 patients and was most frequent in infants. Neutrophilic disease of the upper respiratory tract, as well as cardiac neutrophilic disease, was only observed in infants, whereas other locations were similarly found in infants, young children and adolescents. In infants and young children, ND were associated with a large spectrum of general diseases, whereas in adolescents associations were limited to inflammatory bowel disease and Behçet's disease. Conclusions: Our study describes the concept of ND in paediatric patients and shows that they have some characteristics different from ND occurring in adults. ND occurring in infants can be associated with a large spectrum of general diseases. Occurrence of neutrophilic disease is frequent in children. Thus, ND occurring in young paediatric patients should incite clinicians to schedule complementary explorations in order to search for involvement of other organs and to rule out monogenetic autoinflammatory syndromes.